Flexible cascaded multilevel inverter with multiple operation modes - Wang, Yaoqiang; Du, Guanyu; Liang, Jun; Qin, Ming (JOURNAL OF POWER ELECTRONICS, 2020)
In this paper, a flexible cascaded multilevel inverter is proposed with a wide operational range. The inverter can change its topology structure to operate in three modes by a bidirectional switch unit. The nine-level or five-level mode of the inverter is adopted to optimize the output waveform when the input power is low. To decrease power losses, the three-level mode of the inverter is adopted to reduce the number of active switch devices when the input power is high. The topology and modulation strategy of the proposed inverter are presented and analyzed. The total losses and current THD of the inverter are calculated. In addition, simulations and experiments are conducted. The obtained simulation and experimental results indicate the correctness and feasibility of the proposed inverter and its modulation strategy.